Trends in global amyotrophic lateral sclerosis research from 2000 to 2022: A bibliometric analysis - Shi, Guanzhong; Zhou, Jinxia; Huang, Kun; Bi, Fang-Fang (Frontiers in Neuroscience, 2022)
Background Amyotrophic lateral sclerosis (ALS) is a relentlessly progressive neurodegenerative disease affecting the motor neurons. Although much research has been conducted in this field, few bibliometric studies have been conducted. This study aimed to provide an overview of publishing characteristics and trends in ALS research since 2000 using a bibliometric analysis. Methods We conducted a comprehensive literature search in the Web of Science Core Collection database for scientific output related to ALS from 2000 to 2022. The retrieved dataset was refined using Google OpenRefine and analyzed using bibliometrix. Results A total of 29,391 articles published since 2000 were retrieved, with an average annual growth rate of 6.35%. Ninety-six countries and regions contributed to ALS research, among which the United States had the dominant position with the highest number of publications (n=8,202) and citations (n=558,561). An association analysis was performed to form networks of country collaboration and keyword co-occurrence. The evolution of topic trends was demonstrated in terms of both frequency and proportion. Conclusion The output of ALS research has increased steadily over the years, and the United States and Western Europe are leaders in this field. There is an upgradation in the pathomechanism and clinical research on ALS.